Physicochemical Properties of Patchouli and Trigona’s Honey Functional Hard Candy - Juliani; Irmayanti (Universitas Serambi Mekkah, 2024)
Consumers are experiencing increased awareness of healthy food, including healthy candy. Therefore, sugar in candy was reduced by adding isomalt and trigona honey. Natural flavors such as patchouli oil are also added to replace synthetic flavors in hard candy. This research aims to determine the physicochemical and descriptive properties of patchouli and trigona’s honey hard candy. The data were analyzed descriptively. The result shows that the low-calories hard candy containing Trigonas Honey and Patchouli Oil has yield value range 67.66% - 63.10%, with density value range 2.35 (g/cm3) - 2.18 (g/cm3) and pH value range 4.56 - 3.86. It can be concluded that the hard candy that containing trigona’s honey and patchouli oil has the physicochemical properties that high yield, relatively low density, slightly acidic so further reseach are needed to overcome deficiencies in the physicochemical properties of these functional hard candies.